2014
DOI: 10.1007/7651_2014_191
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Field Gel Electrophoresis

Abstract: Pulse Field Gel Electrophoresis (PFGE) is a powerful genotyping technique used for the separation of large DNA molecules (entire genomic DNA) after digesting it with unique restriction enzymes and applying to a gel matrix under the electric field that periodically changes direction. PFGE is a variation of agarose gel electrophoresis that permits analysis of bacterial DNA fragments over an order of magnitude larger than that with conventional restriction enzyme analysis. It provides a good representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…40 The importance of agr locus has been well established in a variety of animal models of infection. 41 Mechanistically, previous studies have demonstrated that the psm-mec RNA influences virulence, at least in part, by inhibiting the translation of agrA , a key positive regulator of all other PSM subtypes. 32,38 Thus, high PSM-mec production should result in lower production of other PSMs, although it has been shown that this effect and the overall impact on virulence of the psm-mec locus is highly strain-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…40 The importance of agr locus has been well established in a variety of animal models of infection. 41 Mechanistically, previous studies have demonstrated that the psm-mec RNA influences virulence, at least in part, by inhibiting the translation of agrA , a key positive regulator of all other PSM subtypes. 32,38 Thus, high PSM-mec production should result in lower production of other PSMs, although it has been shown that this effect and the overall impact on virulence of the psm-mec locus is highly strain-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Principle Reference agr typing Amplification of the hypervariable segment [86] spa typing Amplification and sequencing of the 24 bp polymorphic zone X of the spa gene [87] Mutilocus sequence typing (MLST) sequence analysis of the allelic variants of the seven housekeeping genes [88] SCCmec typing Analysis of the structure of SCCmec region [89] Pulsed-field gel electrophoresis (PFGE) Macro-restriction profiling based on the digestion of DNA with restriction enzymes [90] Random Amplification of Polymorphic DNA (RAPD)…”
Section: Typing Methodsmentioning
confidence: 99%
“…Organisms involved in acquisition events were analyzed for transmission events using pulsed-field gel electrophoresis (PFGE; see Supplementary Material). 16 Finally, each nurse completed a 4-question survey at the end of the shift to describe how the scrubs worn during the shift compared to their standard work scrubs. Ultimately, each nurse answered 3 surveys, corresponding with each arm in the study.…”
Section: Methodsmentioning
confidence: 99%